CBOE Volatility Index VIX and the Volatility Premium Structure Analysis - Krol, Anastasiia; Witzany, Jiří, 1966-; Chval, David; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2019)
This thesis represents the overview of the relevant information on the CBOE Volatility Index providing theoretical background on definition, estimation and modelling of historical, stochastic and realized volatilities. The main focus is on implied volatility and attributes, such as volatility skew and volatility risk premium, in terms of CAPM model. The described models of volatility estimations include GARCH, ARCH, EMWA, HAR and ARFIMA with modifications. The implied volatility is explained in terms of Black-Scholes option pricing model, Cox-Ross-Rubinstein method and model-free methodology. Further on, the model-free methodology is explained to be the methodological basis of VIX calculations, which are provided along with additional information on index, such as value reading, forecasting ranges of equity market volatility with current levels of index and alternative measures of volatility used by traders, such as ATR, Bollinger Bands and other volatility indexes besides VIX. The third part is essential to understand the framework of trading untradeable index with VIX Futures (VX) and options explained along with an overview of volatility ETP market and analysis of XIV case. The empirical part contains the interpretation of volatility risk premium and its existence, the analysis of development of premium in terms of crisis and testing its structure by comparing its sensitivity to the components. The last part is tackling the volatility risk premium of VX futures with the same approach and compares the two premiums.
Vedoucí práce: Jiří Witzany
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: finanční inženýrství [obor dipl. práce]; diplomové práce; master's theses